Principal Catalyst For Sustainable Rural Development In Imo State - Enwereuzor, Angela (COOU Journal of Multidisciplinary Studies, 2017)
This study is an investigative analysis designed to determine the principal catalyst for sustainable rural development in Imo State. Questionnaire is the main instrument for data collection. Stratified, systematic and random sampling techniques were used in selecting the rural areas. Data from the questionnaire were collected, tabulated in frequency distribution tables and analyzed using percentage ratios, statistical techniques which include factor analysis, analysis of variance and chi-square model. The hypothesis states that rural development is not hinged on a particular infrastructure in rural communities of Imo State. The resultant test of the hypothesis reveals that rural development in Imo State is hinged on a particular infrastructure and that infrastructure is statistically identified as security. The study recommends that every infrastructure meant for development should have security as a vital component to ensure uninterrupted service.